Effect of chocolate milk for muscle recovery in muscular endurance performance / Khairul Ajmal Zaini - Zaini, Khairul Ajmal (Faculty of Sports Science and Recreation, 2018)
Chocolate milk has been shown to be the effective recovery beverage for muscle recovery in muscular endurance exercise. The purpose of this study was to identify the effect of chocolate milk for muscle recovery in muscular endurance performance. A total of 15 subjects (N = 15) from 19 years old to 21 years old (M=19.4, SD=0.632) were chosen via simple random sampling to participate in this study. This study was using cross sectional design, pre and post design with chocolate milk as study treatment. Push up until fatigue have been conducted to measure the effectiveness of chocolate milk for muscle recovery. Using the paired sample t-test, the result showed that there was a significant effect of chocolate milk for muscle recovery in muscular endurance performance (M = -8.533, SD = .632, P = .000). As a conclusion, chocolate milk has muscle recovery properties and showed that similar quality as others recovery beverage.